2005
DOI: 10.1038/sj.onc.1208787
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and progesterone regulate radiation-induced p53 activity in mammary epithelium through TGF-β-dependent pathways

Abstract: DNA damage normally induces p53 activity, but responses to ionizing radiation in the mammary epithelium vary among developmental stages. The following studies examined the hormones and growth factors that regulate radiation-responsiveness of p53 in mouse mammary epithelium. Immunoreactive p21/WAF1 and TUNEL staining were used as indicators of p53 activity following exposure to ionizing radiation. In ovariectomized mice, radiation-induced accumulation of p21/WAF1 was minimal in the mammary epithelial cells (o1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 39 publications
(34 reference statements)
1
44
0
Order By: Relevance
“…It was postulated that the protective effect of hormones in mammary carcinogenesis might, in part, be related to regulation of p53 activation (Becker et al 2005). Proof of principle experiments examining p53-deficient mammary tissues demonstrated a lack of parity-induced protection, confirming the participation of p53 in hormonal-mediated chemoprevention (Medina & Kittrell 2003).…”
Section: Tgf-b and Its Dual Role In Cancermentioning
confidence: 90%
See 3 more Smart Citations
“…It was postulated that the protective effect of hormones in mammary carcinogenesis might, in part, be related to regulation of p53 activation (Becker et al 2005). Proof of principle experiments examining p53-deficient mammary tissues demonstrated a lack of parity-induced protection, confirming the participation of p53 in hormonal-mediated chemoprevention (Medina & Kittrell 2003).…”
Section: Tgf-b and Its Dual Role In Cancermentioning
confidence: 90%
“…Recent analyses demonstrate a direct cross talk between TGF-b and hormones in the process of p53 activation within irradiated mammary epithelium. In ovariectomized mice, systemic injections of estrogen and progesterone were necessary to recover maximal expression of cell cycle regulators following ionizing radiation (Becker et al 2005). While ovarian steroid hormone administration augmented the p53 response to radiation (Becker et al 2005), neutralization of TGF-b blocked responsiveness (Ewan et al 2002b).…”
Section: Tgf-b and Its Dual Role In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The research in our lab has shown that the p53 tumor suppressor pathway is a crucial downstream effector for this protection mechanism 5,6 . Parous mammary epithelium showed significantly higher apoptotic response to ionizing radiation (IR) which was p53-dependent 7,8 . Recent research showed p53 might also participate in the regulation of tissue-specific stem cells 9,10 .…”
Section: Introductionmentioning
confidence: 99%